Question de métonymie dans la traduction automatique - Czekaj, Anna (Neophilologica, 2011)
The article is devoted to the problem of metonymy in automatic translation. The author focuses on possible difficulties that can arise in the process of automatic translation of metonymic structures. The analysis of the problem is largely based on the examples taken from corpus material, which has been collected by the author, referring to the parts of the body and analysed according to the object oriented approach proposed by W. Banyś, as well as on the examples taken from the doctoral dissertation by T. Massoussi, which is devoted to a very thorough classification of various metonymic uses. The author shows how the adopted method of analysing language items can serve as a tool in solving problems that may appear in the process of translating the structures in question.